2(3*x-1)(x-3)=0

Simple and best practice solution for 2(3*x-1)(x-3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3*x-1)(x-3)=0 equation:


Simplifying
2(3x + -1)(x + -3) = 0

Reorder the terms:
2(-1 + 3x)(x + -3) = 0

Reorder the terms:
2(-1 + 3x)(-3 + x) = 0

Multiply (-1 + 3x) * (-3 + x)
2(-1(-3 + x) + 3x * (-3 + x)) = 0
2((-3 * -1 + x * -1) + 3x * (-3 + x)) = 0
2((3 + -1x) + 3x * (-3 + x)) = 0
2(3 + -1x + (-3 * 3x + x * 3x)) = 0
2(3 + -1x + (-9x + 3x2)) = 0

Combine like terms: -1x + -9x = -10x
2(3 + -10x + 3x2) = 0
(3 * 2 + -10x * 2 + 3x2 * 2) = 0
(6 + -20x + 6x2) = 0

Solving
6 + -20x + 6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(3 + -10x + 3x2) = 0

Factor a trinomial.
2((1 + -3x)(3 + -1x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(1 + -3x)' equal to zero and attempt to solve: Simplifying 1 + -3x = 0 Solving 1 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -3x = 0 + -1 -3x = 0 + -1 Combine like terms: 0 + -1 = -1 -3x = -1 Divide each side by '-3'. x = 0.3333333333 Simplifying x = 0.3333333333

Subproblem 2

Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3

Solution

x = {0.3333333333, 3}

See similar equations:

| 2x-5=8x+7-3x | | -4+3x+-1=2x+1+2x | | 4(m+6)=36 | | 5x-6(3)=7 | | 6(4f)=-24f | | 5(-1)-6y=7 | | x*x+6x-5=12 | | 2x+15=-3x+5 | | 2+4r=r-6 | | 8(2)+y=16 | | 81m^2-64=0 | | 8x-0.8=9x | | 4x+12=5x-1 | | 3x+1+51=180 | | 4a+3a-9a= | | K^2-625=0 | | 3x+1=51 | | R=pq | | 8n+3=3(2n)-1 | | n+3-5=12 | | y=-1.25(x-5) | | b+5-20=180 | | 2g+5=32 | | 4x*x-11x+14=8x+2 | | 3x-1.5=6 | | 2x+(3x-12)+(4x+9)=360 | | -7x+14=-8x-16 | | y/4-7=8 | | x+5-10=54 | | 8+-2x=7x+82 | | x+x-5+65=180 | | -7x=8-16 |

Equations solver categories